2018
DOI: 10.1111/ggi.13437
|View full text |Cite
|
Sign up to set email alerts
|

Path analysis of caregiver characteristics and neuropsychiatric symptoms in Alzheimer's disease patients

Abstract: Overburdened caregivers and the use of dysfunctional management strategies are associated with a greater presence of neuropsychiatric symptoms in Alzheimer's disease patients. These aspects should be considered when developing interventions for caregivers to manage neuropsychiatric symptoms and overall treatment of patients with dementia. Geriatr Gerontol Int 2018; 18: 1177-1182.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The sociodemographic characteristics of this study’s sample were similar to previously-reported ones [14,15,16]. Mainly, family caregivers were middle-age females, patients’ daughters or partners and with low academic backgrounds.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The sociodemographic characteristics of this study’s sample were similar to previously-reported ones [14,15,16]. Mainly, family caregivers were middle-age females, patients’ daughters or partners and with low academic backgrounds.…”
Section: Discussionsupporting
confidence: 67%
“…It is also known that family caregivers’ burden can worsen the person-caregiver relationship, which can in turn increase the severity of persons’ neuropsychiatric symptoms [10]. These results may indicate the need for designing and implementing intervention strategies in emotional regulation that allow family caregivers to adapt to the person’s behavior disorders from an early stage of AD [16]. Lastly, a persons’ level of dependency for performing basic activities of their daily lives is another variable that, together with behavioral disorders, produces a great overload in family caregivers of people diagnosed with AD [27,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in educational level that emerged from our study are not supported by other studies. The results of Delfino [ 34 ] showed that female caregivers have a significant difference for burden but no differences emerged for the educational level. Further studies may clarify this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental conditions, caregiver-related factors, neglected needs, patient and caregiver personality, among other variables, can also lead to the manifestation of NPSs. 9 Stress and depression increase when a caregiver manages NPSs, and these symptoms can be triggered or exacerbated when a caregiver is stressed or depressed. 10 The burden experienced by caregivers has many causes, such as the constant and increasing need to supervise the patient, the older adult's physical and cognitive dependence, the lack of support from other family members, family conflicts, financial difficulties, and social deprivation.…”
Section: Introductionmentioning
confidence: 99%